Screening and sensitivity of non-lactose fermenting bacteria to antibiotics by Vitek-2 compact system - Khaleel Ibrahim, Hanaa (University of Thi-Qar Journal of Science, 2019)
We are collected 150 clinical sample from different private veterinary clinics in Basrah province . Included 25 isolates from nasal discharge, 45 from feces , 35 from pus/wound infections, 20 from blood and 25 from ear swab .All isolates were subjected to microscopic examination and diagnosed 4 species of Non- Fermenting Gram Negative Bacilli (NFGNB) bacteria based on 47 biochemical tests by Vitek 2 a compact system where the species were 48 strain (32%) of Pseudomonas aeruginosa , 32 strain (21.33%) of Burkholderia cepacia, 31strain (20.66%) of Sphingomonas paucimobilis, 20 strain (13.33%) of Proteus mirabilis and 19 strain (12.66%) of Acinetobacter calcoaceticus . NFGNB results showed antibiotic susceptibility to different antibiotic resistance and susceptibility, where isolates showed Pseudomonas aeruginosa, Burkholderia cepacia and Proteus mirabilis were susceptibility to antibiotic Meropenem (80% -98%), while Acinetobacter spp, Pseudomonas aeruginosa least susceptible to Cefuroxime and Trimethoprim/Sulfamethoxazole (20% – 30%). The bacteria showed Sphingomonas paucimobilis showed resistance to all the antibiotics tested. The current study was carried out with the aim of diagnosing and identifying NFGNB isolated from clinical samples and evaluating their clinical importance and study of antibiotic resistance.